Recovery, analysis and storage of quartz assemblages - recommendations (Scottish Historical and Archaeological Internet Reports, 2008)
The research into archaeological quartz has three main stages, namely: recovery of quartz artefacts and assemblages in the field; analysis of the recovered quartz finds in the laboratory; and storage of the recovered quartz. These are interconnected, in the sense that the initial choice of recovery policy defines which inference may be made at a later stage, and how detailed this inference can become, and it defines the museum storage requirements.